Slow Receptor Dissociation Kinetics Differentiate Macitentan from Other Endothelin Receptor Antagonists in Pulmonary Arterial Smooth Muscle Cells - Gatfield, John; Mueller Grandjean, Celia; Sasse, Thomas; Clozel, Martine; Nayler, Oliver (PLOS ONE, 2012)
Two endothelin receptor antagonists (ERAs), bosentan and ambrisentan, are currently approved for the treatment of pulmonary arterial hypertension (PAH), a devastating disease involving an activated endothelin system and aberrant contraction and proliferation of pulmonary arterial smooth muscle cells (PASMC). The novel ERA macitentan has recently concluded testing in a Phase III morbidity/mortality clinical trial in PAH patients. Since the association and dissociation rates of G protein-coupled receptor antagonists can influence their pharmacological activity in vivo, we used human PASMC to characterize inhibitory potency and receptor inhibition kinetics of macitentan, ambrisentan and bosentan using calcium release and inositol-1-phosphate (IP1) assays. In calcium release assays macitentan, ambrisentan and bosentan were highly potent ERAs with Kb values of 0.14 nM, 0.12 nM and 1.1 nM, respectively. Macitentan, but not ambrisentan and bosentan, displayed slow apparent receptor association kinetics as evidenced by increased antagonistic potency upon prolongation of antagonist pre-incubation times. In compound washout experiments, macitentan displayed a significantly lower receptor dissociation rate and longer receptor occupancy half-life (ROt1/2) compared to bosentan and ambrisentan (ROt1/2∶17 minutes versus 70 seconds and 40 seconds, respectively). Because of its lower dissociation rate macitentan behaved as an insurmountable antagonist in calcium release and IP1 assays, and unlike bosentan and ambrisentan it blocked endothelin receptor activation across a wide range of endothelin-1 (ET-1) concentrations. However, prolongation of the ET-1 stimulation time beyond ROt1/2 rendered macitentan a surmountable antagonist, revealing its competitive binding mode. Bosentan and ambrisentan behaved as surmountable antagonists irrespective of the assay duration and they lacked inhibitory activity at high ET-1 concentrations. Thus, macitentan is a competitive ERA with significantly slower receptor dissociation kinetics than the currently approved ERAs. Slow dissociation caused insurmountable antagonism in functional PASMC-based assays and this could contribute to an enhanced pharmacological activity of macitentan in ET-1-dependent pathologies.